Inter-sector relationships, scientific output and national policies for research development: a case study on Cuba 2003-2007 - Arencibia Jorge, Ricardo; Corera Alvarez, Elena; Chinchilla Rodríguez, Zaida; Moya Anegón, Félix de (Revista Cubana de Información en Ciencias de la Salud, 2013)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The scientific output of research sectors involved in Cuban R&D activities during the period 2003-2007, using Scopus as data source, was analyzed. Quantitative and qualitative dimension of the scientific production was described through a set of bibliometric indicators. The most productive and visible sectors were identified. The evolution of the total scientific output by sector, and the behavior of the three most important sectors were studied. Inter-sector relationships were visualized with the aim to analyze the national scientific macro-structure. The growth of Higher Education and Health Sector determined the nation's growth during this period. Despite a positive evolution of the Cuban scientific output, a weak linkage between universities and institutions of science and technological innovation, and also scarce relationships between scientific research centers and health institutions, were observed. Low indices of international collaboration in Health Sector, and deficient links between R&D units of enterprises and institutions belonging to Higher Education and Science and Technology, were also identified.